To What degree practice situational leadership principles by government principals’ schools in BaniKenana Metropolitan area as perceived by teachers - Canaan, Mustafa Mohamed Hadi (Journal of Educational and Psychological Sciences, 2019)
The purpose of this study was to explore the degree of applying situational leadership principles by principals in BaniKenana Metropolitan area as perceived by teachers in the light of several variables such as: gender, scientific qualification , and years of experience. The sample of the study consisted of (520) male and female teachers chosen randomly as they responded to questionnaire consisted of (25) items distributed in five domains: Planning, Decision making, Execution, Evaluation and relations with teachers. The suitable statistical measures were obtained, as the findings were as follows: The degree of applying situational leadership by principals in BaniKenanaMetropolitan area is moderate with a mean of (3.20from5),about fields, the field of teacher relationships was the highest with mean (3.51)with high grade then planning with mean (3.38) then evaluation with mean (3.19) then decision making with mean (3.15) then implementation with mean (2.76) and all of them with medium grade. There were no significant statistical differences at the level of α = 0.05 between the means of samples responses about the degree of Appling situational leadership by principals in BaniKenana Metropolitan area due to gender and scientific qualification variables, and there were significant statistical differences at the level of α = 0.05 between the means of samples responses about the degree of applying situational leadership by principals in BaniKenana Metropolitan area due experience variable for the favor of less than 5 years experience. The study recommended the involvement of teachers in the decision-making process within the schools.